PENGARUH MEDIA E MODUL TERHADAP HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN ISLAMIC FAITH EDUCATION DI SEKOLAH MENENGAH PERTAMA AL ABIDIN BILINGUAL BOARDING SCHOOL SURAKARTA TAHUN PELAJARAN 2024/2025 - Halimah, Izzah Noer; Fathurrohman, Mukhlis (STKIP Pesisir Selatan, 2025)
This study examined whether e‑module use predicts Islamic Faith Education (IFE) achievement among Grade‑VII students at Al‑Abidin Bilingual Boarding School, Surakarta. A quantitative design with census sampling was applied; the population and sample comprised 58 students. The predictor (X) was measured with a 1–5 Likert questionnaire; twenty items were trialed, nineteen retained as valid, and internal consistency reached Cronbach’s alpha = 0.883. The outcome (Y) used official IFE report‑card scores. Analyses covered descriptive statistics, Kolmogorov–Smirnov normality, linearity, Pearson correlation, and coefficient of determination (SPSS 24). A 30‑student pilot supported item validity; analyses used individual‑level pairing. E‑module use was moderately high (M = 70.97; SD = 11.48; range 45–93). IFE achievement was high (M = 87.78; SD = 9.39; range 20–94). Assumptions were met: residuals were normally distributed (p = 0.200) and the X–Y relation was linear (p = 0.268). The Pearson correlation was positive yet weak and non‑significant (r = 0.215; p = 0.104); the explanatory power was small (R² = 0.046; Adjusted R² = 0.029). About 4.6% of score variance was accounted for by e‑module use.